Modulation of toxin stability by 4-phenylbutyric acid and negatively charged phospholipids. - Supriyo Ray (PLoS ONE, 2011)
AB toxins such as ricin and cholera toxin (CT) consist of an enzymatic A domain and a receptor-binding B domain. After endocytosis of the surface-bound toxin, both ricin and CT are transported by vesicle carriers to the endoplasmic reticulum (ER). The A subunit then dissociates from its holotoxin, unfolds, and crosses the ER membrane to reach its cytosolic target. Since protein unfolding at physiological temperature and neutral pH allows the dissociated A chain to attain a translocation-competent state for export to the cytosol, the underlying regulatory mechanisms of toxin unfolding are of paramount biological interest. Here we report a biophysical analysis of the effects of anionic phospholipid membranes and two chemical chaperones, 4-phenylbutyric acid (PBA) and glycerol, on the thermal stabilities and the toxic potencies of ricin toxin A chain (RTA) and CT A1 chain (CTA1). Phospholipid vesicles that mimic the ER membrane dramatically decreased the thermal stability of RTA but not CTA1. PBA and glycerol both inhibited the thermal disordering of RTA, but only glycerol could reverse the destabilizing effect of anionic phospholipids. In contrast, PBA was able to increase the thermal stability of CTA1 in the presence of anionic phospholipids. PBA inhibits cellular intoxication by CT but not ricin, which is explained by its ability to stabilize CTA1 and its inability to reverse the destabilizing effect of membranes on RTA. Our data highlight the toxin-specific intracellular events underlying ER-to-cytosol translocation of the toxin A chain and identify a potential means to supplement the long-term stabilization of toxin vaccines.